Corporate governance : principles, policies and practices - Fernando, A. C. (Chennai Pearson Education, 2012)
The second edition of A. C. Fernando's bestselling Corporate Governance: Principles, Policies and Practices sheds light on recent corporate problems using a flexible modular format, through a detailed explanation of the corporate governance mechanism and the various incentives within today's governance system, while offering potential solutions in context. With an emphasis on connecting corporate governance to practical management, the book provides cutting-edge material comprising new and unique study tools and fresh, thought-provoking content.
Kindle eBook.